2021
DOI: 10.1001/jamacardio.2021.3370
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Atrial Fibrillation and the Prevalence of Rare Variants in Cardiomyopathy and Arrhythmia Genes

Abstract: IMPORTANCE Early-onset atrial fibrillation (AF) can be the initial manifestation of a more serious underlying inherited cardiomyopathy or arrhythmia syndrome.OBJECTIVE To examine the results of genetic testing for early-onset AF. DESIGN, SETTING, AND PARTICIPANTSThis prospective, observational cohort study enrolled participants from an academic medical center who had AF diagnosed before 66 years of age and underwent whole genome sequencing through the National Heart, Lung, and Blood Institute's Trans-Omics for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 52 publications
6
85
0
3
Order By: Relevance
“…This risk likely comes from two mechanisms. First, rare monogenic mutations in channels and gap junction proteins with large effect sizes occur in families with AF [ 34 ] and are more common in early-onset AF [ 35 ]. This includes germline mutations that pass to descendants as well as somatic mutations.…”
Section: Pathophysiology Of Af At the Genetic Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk likely comes from two mechanisms. First, rare monogenic mutations in channels and gap junction proteins with large effect sizes occur in families with AF [ 34 ] and are more common in early-onset AF [ 35 ]. This includes germline mutations that pass to descendants as well as somatic mutations.…”
Section: Pathophysiology Of Af At the Genetic Levelmentioning
confidence: 99%
“…This includes germline mutations that pass to descendants as well as somatic mutations. When identified, such features motivate family screening to identify early-onset AF [ 35 ]. Second, common variations in a network of over 100 genes now identified from genome-wide association studies (GWAS) confer a smaller, yet additive, risk for AF [ 36 ].…”
Section: Pathophysiology Of Af At the Genetic Levelmentioning
confidence: 99%
“…However, in the thin filament subgroup, AF tends to onset at younger age ( Bongini et al, 2016 ) and is more often aggressively treated with catheter ablation ( Coppini et al, 2014 ). Indeed, in a recent prospective observational cohort study on more than 1,200 patients with early-onset AF (<66 years) ( Yoneda et al, 2021 ), the cardiomyopathy-gene panel test identified a pathogenic sarcomere mutation in 10% of patients. This pivotal study supports the use of genetic testing in early-onset AF, although the clinical association between sarcomere mutation and AF remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…5 They found 3.1% had a loss-of-function variant in a cardiomyopathy-associated gene. In a larger study of young-onset (<66 years) but otherwise unselected AF patients, 6 the yield of disease-associated variants in cardiomyopathy and arrhythmia syndrome genes was 10.1%, increasing to 16.8% in those aged <30 years at the time of presentation with AF. The most commonly implicated genes were all associated with cardiomyopathy ( TTN [29%], MYH7 [14%], MYH6 [8%], and LMNA [6%]).…”
mentioning
confidence: 94%